2010
DOI: 10.1177/172460081002500307
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Plasma and Serum Osteopontin Levels: Usefulness in Diagnosis of Epithelial Malignant Pleural Mesothelioma

Abstract: These data suggest that plasma OPN and serum OPN are not influenced by confounding factors such as age, smoking habits and asbestos exposure. Plasma and serum OPN may be useful markers in the diagnosis of epithelial MPM in addition to traditional radiological exams. However, in our opinion plasma OPN is preferable to serum OPN because it is more stable and measurements of OPN in serum are less reliable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 23 publications
1
35
1
Order By: Relevance
“…A French study reported higher osteopontin levels in plasma compared to serum, but showed that the ability of osteopontin to discriminate between patients with MM and healthy asbestosexposed subjects was similar using either plasma or serum [28]. However, other studies suggest that plasma is superior to serum when assaying osteopontin levels with a view to discriminating between MM and control patients [58]. On the contrary, the choice of blood sample type has limited effect on soluble mesothelin sensitivity [59].…”
Section: Osteopontinmentioning
confidence: 90%
“…A French study reported higher osteopontin levels in plasma compared to serum, but showed that the ability of osteopontin to discriminate between patients with MM and healthy asbestosexposed subjects was similar using either plasma or serum [28]. However, other studies suggest that plasma is superior to serum when assaying osteopontin levels with a view to discriminating between MM and control patients [58]. On the contrary, the choice of blood sample type has limited effect on soluble mesothelin sensitivity [59].…”
Section: Osteopontinmentioning
confidence: 90%
“…Recent studies suggest that OPN and related molecules are a potential target for anticancer therapy. In addition, the plasma concentration of OPN in patients with tumor metastasis is significantly increased in comparison to normal sera, thus its prospects as a marker for evaluating tumor genesis and metastasis are expected (22)(23)(24). Accordingly, further research on OPN is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the recovery of HE4 rises over 200% after 48 h. Again, OPN is the only marker showing a decline to nearly 80% in recovery supporting our above mentioned findings. Also, Cristaudo et al [30] found an instable performance of OPN after storage of serum samples at room temperature.…”
mentioning
confidence: 99%